Zuboriosba Lasko : François Bouillon - Dominique Labauvie - Osman - François Righi - Vladimir Skoda - Hans Van Den Ban - Jean Zuber. - Bataillon, Françoise; Galerie Bernard Jordan, Paris (Paris : Galerie Philippe Casini, 1987)
François Bouillon - Dominique Labauvie - Osman - François Righi - Vladimir Skoda - Hans Van Den Ban - Jean Zuber
Zuboriosba Lasko : François Bouillon - Dominique Labauvie - Osman - François Righi - Vladimir Skoda - Hans Van Den Ban - Jean Zuber, Galerie Philippe Casini, Paris ; Galerie Bernard Jordan, Paris, 1987
boek